Interviewing Roomba: A posthuman study of humans and robot vacuum cleaners. Issue 3 (1st September 2020) - Gross, Jennifer
Roomba, the autonomous robotic vacuum cleaner sold by iRobot since 2002, is now a taken-for-granted household helper in many homes. In this study that cross-cuts phenomenology, postphenomenology, actor–network theory and media ecology, I utilize four heuristics for interviewing digital objects. I interview Roomba and utilize qualitative research methods to theorize about the complexities of the entanglements and relationships between human beings and their robot vacuum cleaners. Conclusions connect to critical theory and feminism and also question justifications of anthropocentrism in a posthuman world.